The Cognitive Neuroscience of Stable and Flexible Semantic Typicality - Folstein, Jonathan R.; Dieciuc, Michael A. (Frontiers in Psychology, 2019)
Typicality effects are among the most well studied phenomena in the study of concepts. The classical notion of typicality is that typical concepts share many features with category co-members and few features with members of contrast categories. However, this notion was challenged by evidence that typicality is highly context dependent and not always dependent on central tendency. Dieciuc and Folstein (in press) argued that there is strong evidence for both views and that the two types of typicality effects might depend on different mechanisms. A recent theoretical framework, the Controlled Semantic Cognition framework (Lamdon Ralph, Jefferies, Patterson, & Rogers, 2017) strongly emphasizes the classical view, but includes mechanisms that could potentially account for both kinds of typicality. In contrast, the Situated Cognition framework (Barsalou, 2009b) articulates the context dependent view. Here we review evidence from cognitive neuroscience supporting the two frameworks. We also briefly evaluate the ability of computational models associated with the CSC to account for phenomena supporting SitCog (Rogers & McClelland, 2004). Many predictions of both frameworks are born out by recent cognitive neuroscience evidence. While the CSC framework can at least potentially account for may of the typicality phenomena reviewed, challenges remain, especially with regards to ad hoc categories.